Rev-erbα Negatively Regulates Osteoclast and Osteoblast Differentiation through p38 MAPK Signaling Pathway - Kim, Kabsun (Mol Cells, 2020)
The circadian clock regulates various physiological processes, including bone metabolism. The nuclear receptors Rev-erbs, comprising Rev-erbα and Rev-erbβ, play a key role as transcriptional regulators of the circadian clock. In this study, we demonstrate that Rev-erbs negatively regulate differentiation of osteoclasts and osteoblasts. The knockdown of Rev-erbα in osteoclast precursor cells enhanced receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast formation, as well as expression of nuclear factor of activated T cells 1 (NFATc1), osteoclast-associated receptor (OSCAR), and tartrate-resistant acid phosphatase (TRAP). The overexpression of Rev-erbα leads to attenuation of the NFATc1 expression via inhibition of recruitment of c-Fos to the NFATc1 promoter. The overexpression of Rev-erbα in osteoblast precursors attenuated the expression of osteoblast marker genes including Runx2, alkaline phosphatase (ALP), bone sialoprotein (BSP), and osteocalcin (OC). Rev-erbα interfered with the recruitment of Runx2 to the promoter region of the target genes. Conversely, knockdown of Rev-erbα in the osteoblast precursors enhanced the osteoblast differentiation and function. In addition, Rev-erbα negatively regulated osteoclast and osteoblast differentiation by suppressing the p38 MAPK pathway. Furthermore, intraperitoneal administration of GSK4112, a Rev-erb agonist, protects RANKL-induced bone loss via inhibition of osteoclast differentiation in vivo. Taken together, our results demonstrate a molecular mechanism of Rev-erbs in the bone remodeling, and provide a molecular basis for a potential therapeutic target for treatment of bone disease characterized by excessive bone resorption.